The surprising role of marital status on sport second-screening: demographic influences during the 2022 world cup viewing in Israel - Galily, Yair; Samuel-Azran, Tal; Laor, Tal (Frontiers in Sports and Active Living, 2024)
To better understand what characterizes those who use a second screen while watching sport, the study examine a variety of demographic factors influencing browsing device trends before, during (“second screen”), and after sports games. It does so by utilizing survey data from Israeli viewers of the 2022 World Cup using a convenience sample (N = 242). In line with our hypotheses, those with higher education and higher reported income were more likely to browse devices for information around and during games. Against our hypothesis, young adults were less likely to engage in browsing before, during and after the games, possibly because they tend to watch games with friends or in public places. Divorced and single individuals are more likely to engage in multi-platform browsing and second-screening during sport games vs. married participants, who tended to watch the games with friends or in public places. The results are the first to indicate the important role of marital status in second-screening during sport games. Overall, they depict a picture of the average second-screener as a non-married older male with higher income and education, thus indicating that higher intellect combined with non-marital status, thus potentially more spare time as well as possibly higher levels of loneliness and during games are linked to sport second-screening. The results are the first to highlight the important role of marital status over young age on the tendency to second screen during sport games.